2021
DOI: 10.3389/fendo.2020.620466
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Gut, Healthy Bones: Targeting the Gut Microbiome to Promote Bone Health

Abstract: Over the past decade, the use of probiotics to modify the gut microbiome has become a public spotlight in reducing the severity of a number of chronic diseases such as autoimmune disease, diabetes, cancer and cardiovascular disease. Recently, the gut microbiome has been shown to play an important role in regulating bone mass. Therefore, targeting the gut microbiome may be a potential alternative avenue for those with osteopenia or osteoporosis. In this mini-review, we take the opportunity to delve into how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…The results of L. I. Sidorchuk & A. S. Sidorchuk (2018) also suggest the development of intestinal absorption disorders in experimental animals with hypothyroidism due to reduced colonization resistance of the colonic mucosa, the development of dysbiosis, and contamination and colonization of the epithelial biofilm by mucosal microorganisms (Pacifici, 2021). Insufficient supply of calcium in the bloodstream after its absorption triggers the mechanism of bone resorption with the participation of parathyroid hormone (Cooney et al, 2021), as shown by our studies of bone tissue of rats with hypothyroidism Our assumption that the reason for the decrease in the absorption of calcium in the small intestine in hypothyroidism may be induced by mercazolyl pathological processes not only in the intestine but also in the entire digestive tract was confirmed by the biochemical studies of gums and gastric mucosa, small and large intestines. We found the development of oxidative stress, inflammatory and dysbiotic processes against the background of reduced antimicrobial and antioxidant protection in the mouth, stomach and intestines of animals with experimental hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The results of L. I. Sidorchuk & A. S. Sidorchuk (2018) also suggest the development of intestinal absorption disorders in experimental animals with hypothyroidism due to reduced colonization resistance of the colonic mucosa, the development of dysbiosis, and contamination and colonization of the epithelial biofilm by mucosal microorganisms (Pacifici, 2021). Insufficient supply of calcium in the bloodstream after its absorption triggers the mechanism of bone resorption with the participation of parathyroid hormone (Cooney et al, 2021), as shown by our studies of bone tissue of rats with hypothyroidism Our assumption that the reason for the decrease in the absorption of calcium in the small intestine in hypothyroidism may be induced by mercazolyl pathological processes not only in the intestine but also in the entire digestive tract was confirmed by the biochemical studies of gums and gastric mucosa, small and large intestines. We found the development of oxidative stress, inflammatory and dysbiotic processes against the background of reduced antimicrobial and antioxidant protection in the mouth, stomach and intestines of animals with experimental hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs produced by intestinal ora through fermenting dietary bers have the ability to inhibit bone resorption without affecting bone formation [10]. Additionally, intestinal microbes can regulate the differentiation and apoptosis of osteoclast by controlling the dynamic balance of Th-17/Treg cell [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs produced by intestinal flora through fermenting dietary fibers have the ability to inhibit bone resorption without affecting bone formation [ 10 ]. Additionally, intestinal microbes can regulate the differentiation and apoptosis of osteoclast by controlling the dynamic balance of Th-17/T-reg cell [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%